(untitled) (Annual of the Faculty of Philosophy in Skopje, 2010)
The inspiration for the selected paper has been the content of the syllabus of the subject of Group social work, thought on the University level of education of social workers. This topic examines the impact of interactions in small groups in the process of solving complex social problems. Power is one of the phenomena important for the functioning of small group. One way of analysing this phenomenon is through its distribution in the group, its centres of power, roles and the status of individual, leadership etc.